Investigation of external oil flow from a journal bearing in an epicyclic gearbox - Berthold, Martin (2021)
High loads and bearing life requirements make journal bearings the preferred choice for use in planetary gearboxes in aero-engines. Due to the high power being transmitted, large oil quantities are required for cooling and lubrication purposes. A significant part of the total gear box oil flow rate is directed to the journal bearings, which are therefore potentially a major source for load-independent power losses. Journal bearing oil outflow has not yet been comprehensively reviewed. The research work presented in this thesis aims to close this knowledge gap by developing a validated methodology to analyse and evaluate external oil flow from a journal bearing. Thus, new design rules and guidelines to improve epicyclic gearbox performance shall be facilitated. This is achieved by a combination of transient multiphase computational fluid dynamics (CFD) analyses of non-orbiting and orbiting journal bearings using the Volume of Fluid (VOF) method and experimental rig testing with a simplified journal bearing geometry. For numerical fluid flow investigations, the application of representative boundary conditions is imperative. Therefore, an inlet boundary condition was developed to allow the modelling of external oil flow without the need to determine the flow characteristics inside the journal bearing’s lubricating gap by CFD analyses. Numerical analyses showed that, depending on the liquid properties and the operating conditions, two fundamentally different outflow directions and different liquid disintegration regimes occur. Validation of these results was performed through analytical considerations and by experiments. Rig testing was focused on confirming both the outflow direction and the liquid disintegration regimes. An additional outcome was the generation of flow maps, which allow the flow path direction and the liquid disintegration regime to be predicted empirically based on the liquid properties and the operating conditions. Establishing a validated methodology for investigating external oil flow from a journal bearing allowed recommendations for design improvements to be made. These help to maximise gearbox efficiency by minimising the load-independent power losses caused by oil emerging from the journal bearings.